Improved taste and texture in novel popcorn varieties compared to conventional lines. Issue 5 (16th June 2021) - Parsons, Leandra; Rodriguez, Oscar; Holding, David R.
Abstract: Quality Protein Popcorn (QPP) varieties were bred out of a unique germplasm pool derived from Quality Protein dent Maize and conventional popcorn lines. To identify and compare distinctive characteristics within this population, a new sensory method was employed that coupled hedonic numeric rankings of common sensory traits appearance, aroma, texture, and taste with an "overall likability" score while requiring the selection of specific descriptors for taste and texture. Participants tasted six popcorn cultivars, rated each sample based on sensory factors, and offered specific descriptors for taste and texture. This sensory method identified two QPP hybrids with higher overall likability rankings likely attributed to the diversified and improved taste and texture of QPP compared to the controls. The experimental design employed for this descriptive analysis was successful in identifying trait correlations, potential consumer preferences, and ranking of product acceptability and may serve as an efficient model for other sensory studies. Practical Application: Quality Protein Popcorn cultivars are novel products due to their unique genetic composition of elite popcorn and Quality Protein Maize dent maize. To evaluate consumer acceptability of these novel products, a new method for the sensory evaluation of common traits—appearance, aroma, texture, taste, and overall likability—was generated to identify desirable popcorn hybrids and correlations between overall likability and certain sensory attributes. Utilizing a numerical ranking system and categorical key descriptors, this study identified desirable popcorn characteristics and suggested explanations for these attributes. The evaluation format and experimental design employed enabled the identification of significant differences, trends, and correlations between traits and overall likability in a tested population of 112. These methods are easily transferable and may serve as an efficient model for other sensory studies identifying trait correlations, consumer preferences, and ranking of product acceptability. Abstract :